2015
DOI: 10.1093/rheumatology/kev326
|View full text |Cite
|
Sign up to set email alerts
|

Inefficacy of ultrasound-guided local injections of autologous conditioned plasma for recent epicondylitis: results of a double-blind placebo-controlled randomized clinical trial with one-year follow-up

Abstract: ClinicalTrials.gov; https://clinicaltrials.gov/; NCT02378285.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 28 publications
2
68
0
1
Order By: Relevance
“…These results confirm previous network meta-analysis comparing PRP, autologous blood and CS [72]. However, PRP was not effective in patients with first episode epicondylopathy in a RCT [73].…”
Section: Tendinopathiessupporting
confidence: 89%
“…These results confirm previous network meta-analysis comparing PRP, autologous blood and CS [72]. However, PRP was not effective in patients with first episode epicondylopathy in a RCT [73].…”
Section: Tendinopathiessupporting
confidence: 89%
“…There are conflicting results regarding the effectiveness of PRP in the literature. In the study conducted by Montalvan et al, 11 25 patients were assigned into two groups in which PRP were injected twice over a period of four weeks in the study group and normal saline was injected in the control group. Patients were evaluated for VAS on first, third, sixth, and 12 th months.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar blinded RCT involving 50 patients, Schö et al (15) found no clinical differences at 6 months of follow-up. Montalvan et al (16) found in a RCT involving 50 patients between 2 in ltrations of PRP and saline no clinical differences at 6 months of follow-up. Rehabilitation was not allowed during the trial and the tendon was not peppered.…”
Section: Introductionmentioning
confidence: 93%